THE INFLUENCE OF DIGITAL MARKETING ON INCREASING SALES OF FASHION PRODUCTS ON FACEBOOK - Miftahul Jannah; Seny Luhriyani Sunusi; Andi Hajar (International Journal of Business English and Communication, 2026)
This study aims to analyze the influence of digital marketing through the Facebook platform on increasing sales of fashion products in Lasusua, Kolaka Utara. The research is motivated by the limited utilization of digital tools by MSME actors, despite the significant potential offered by Facebook. The research gap lies in the lack of studies focusing on rural areas. A descriptive quantitative method was employed, with 40 business actors participating as respondents. Pearson correlation and regression analysis revealed a very strong relationship (r = 0.956), with 91.4% of the variation in sales being explained by digital marketing. The regression coefficient (0.601) indicates that a one-point increase in digital marketing activity results in a 0.601-point rise in sales. However, usage remains limited to photo uploads; Facebook Live and Ads are rarely used. Cash on delivery (COD) remains the primary payment method. These findings highlight the need for capacity building among business actors to optimize their digital marketing efforts. This research makes a practical contribution to the development of digital strategies for rural MSMEs.